2004
DOI: 10.2135/cropsci2004.1689
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Influence of Neotyphodium Endophytes on Plant Growth and Seed Yield of Lolium perenne Genotypes

Abstract: The aim of this study was to investigate whether Neoptyphodium spp. endophytes, fungal symbionts of cool‐season grasses, can be selected to improve plant growth and seed yield of perennial ryegrass (Lolium perenne L.). Endophyte‐infected (EI) and endophyte‐free (EF) clones of 13 L. perenne genotypes, collected from native habitats with stressful environmental conditions, were evaluated in a field experiment for symbiotic effects on plant growth (herbage yield, reproductive tiller number), seed production, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…In addition, the tissues analysed in our studies represent both source (plants' photosynthetic carbon fixation) and sink (heterotrophic fungus) tissue, making it very difficult to distinguish between source and sink processes. Nevertheless, negative impacts of Neotyphodium endophytes on plant performance and growth in natural ecosystems, especially under severe resource limitations (Cheplick et al 1989(Cheplick et al , 2000Faeth and Sullivan 2003;Cheplick 2004Cheplick , 2007Hesse et al 2004;Faeth and Hamilton 2006), could result in higher concentrations of endophytes under these conditions (as seen in our studies), resulting in increased metabolic demands by endophytes on their host plants.…”
Section: Effects Of N Lolii Endophytes On Host Plant Metabolic Compomentioning
confidence: 51%
“…In addition, the tissues analysed in our studies represent both source (plants' photosynthetic carbon fixation) and sink (heterotrophic fungus) tissue, making it very difficult to distinguish between source and sink processes. Nevertheless, negative impacts of Neotyphodium endophytes on plant performance and growth in natural ecosystems, especially under severe resource limitations (Cheplick et al 1989(Cheplick et al , 2000Faeth and Sullivan 2003;Cheplick 2004Cheplick , 2007Hesse et al 2004;Faeth and Hamilton 2006), could result in higher concentrations of endophytes under these conditions (as seen in our studies), resulting in increased metabolic demands by endophytes on their host plants.…”
Section: Effects Of N Lolii Endophytes On Host Plant Metabolic Compomentioning
confidence: 51%
“…and sheep fescue (Festuca ovina) seedlings analyzed without random factors Seedlings were grown in a greenhouse. SigniWcant P values (P < 0.05) are shown in bold and P < 0.1 are shown in italics from the same habitat or seeds from meadows, indicating that responses of endophyte-infected and endophyte-free grasses can be conditional on seed origin and environmental conditions (see, e.g., Clay 1987;Rice et al 1990;Bacon 1993;Hesse et al 2004;Gundel et al 2006). Seedling establishment in both Wne fescue species was strongly aVected by seed family.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic costs for host plants harboring foliar endophytes have been implied to be the cause of negative impacts on plant performance and growth seen especially in natural ecosystems or under severe resource limitations (Cheplick et al, 1989(Cheplick et al, , 2000Faeth and Sullivan, 2003;Cheplick, 2004Cheplick, , 2007Faeth et al, 2004;Hesse et al, 2004;Faeth and Hamilton, 2006). In plants infected with mycorrhizal fungi the increased costs due to carbon flow to the fungus can be offset by increases in photosynthesis (Wright et al, 1998) and improved plant nutrition (Smith et al, 2001).…”
Section: Effects Of Endophyte Infectionmentioning
confidence: 99%
“…Much less is known about the impacts of fungal endophytes on other plant performance parameters and metabolism, although endophyte infection has been implicated in increasing drought and mineral stress tolerance (Malinowski et al, 1998b;Malinowski and Belesky, 2000;Hesse et al, 2003Hesse et al, , 2005. However, the general mutualistic nature of this particular type of plant-fungus association has been disputed (Saikkonen et al, , 2007Mü ller and Krauss, 2005) and it was shown that positive effects of the endophyte on plant performance depend on genetic variation in the host and endophyte, and on nutrient availability (Cheplick et al, 1989(Cheplick et al, , 2000Cheplick, 2004Cheplick, , 2007Hesse et al, 2004). This link between resource availability and beneficial or neutral versus detrimental effects on plant performance suggests a metabolic cost of the endophyte to the host plant and recent publications indicate that metabolic effects of endophyte infection beyond the accumulation of alkaloids are of importance to the understanding of ecosystem wide impacts of this symbiosis (Hunt et al, 2005;Krauss et al, 2007;Rasmussen et al, 2007).…”
mentioning
confidence: 99%